Amorphous alumina supercapacitors with voltage-charging performance. (1st February 2023) - Fukuhara, Mikio; Yokotsuka, Tomonori; Hashida, Toshiyuki; Yamaguchi, Koji; Fujima, Nobuhisa
Abstract: The electric storage effect of fast charging by voltage application for amorphous alumina (cAAO) supercapacitors fabricated using a crystalline aluminum alloy was investigated in terms of charging/discharging behaviors and AC impedance. The mechanism for the electrical storage of a cAAO supercapacitor was proposed based on the coupling of electrons on Al atoms and positively charged holes in Al vacancies, using an electric double-layer model containing an electrolyte with an electrical resistivity of 6.3 × 10 5 Ωcm. The supercapacitor demonstrated fast charging at a voltage application of up to 500 V.